Genetically Predicted Serum 25‐Hydroxyvitamin D Concentrations in Related to Type 2 Diabetes Mellitus: A Mendelian Randomization Study - Jin Yang (Endocrinology, Diabetes & Metabolism)
ABSTRACT Background In several observational studies, vitamins B6, B9, B12, C and 25‐hydroxyvitamin D[25(OH)D] concentrations were associated with type 2 diabetes mellitus (T2DM). Although vitamins play a role in the development of type 2 diabetes mellitus (T2DM), their associations remain unclear. Objective This study employed Mendelian randomisation (MR) to explore the causal relationships between circulating concentrations of vitamins B6, B9, B12, C, 25‐hydroxyvitamin D and T2DM. Methods Single‐nucleotide polymorphisms (SNPs) linked to vitamin B6, vitamin B9, vitamin B12, vitamin C and 25(OH)D levels were used as instrumental variables (IVs) in this study. We have two outcomes related to T2DM derived from two genome‐wide association studies (GWAS). The first study, referenced by PMID: 3417140, encompasses a cohort of 406,831 individuals of European descent. The second study, identified by PMID: 29892013, includes a sample size of 468,298 Europeans. Results Both univariable Mendelian randomization (UVMR) and multivariable Mendelian randomization (MVMR) analyses demonstrate that genetically predicted elevated levels of serum 25(OH)D are consistently associated with a reduced risk of T2DM. In the UVMR analyses, A 1‐SD increase in genetically predicted serum 25(OH)D levels, the inverse‐variance weighted (IVW) p = 3.8 × 10−7, pfdr = 7.6 × 10−7, the odds ratio(OR) of T2DM (GCST90013942) was 0.67, 95% confidence interval (CI): 0.57–0.78. Furthermore, a 1‐SD increase in genetically predicted serum 25(OH)D levels was associated with an OR of 0.987 for T2DM (GCST90029024), the IVW p = 1.1 × 10−4, pfdr = 1.1 × 10−4 with a 95% CI of 0.981–0.994. In the MVMR analyses, genetically predicted higher serum 25(OH)D levels were associated with a decreased risk of T2DM by the IVW p = 1.2 × 10−5, pfdr = 5.9 × 10−5 in GCST90013942 and IVW p = 4.9 × 10−4, pfdr = 2.5 × 10−3 in GCST90029024. In contrast, levels of vitamins B6, B9, B12, and C did not domenstrate a significant association with T2DM. Conclusion Our research reveals that higher circulating serum 25(OH)D levels reduce the possibility of T2DM.